Tax Rates and Revenue Changes: Behavioural and Structural Factors - John Creedy; Norman Gemmell (New Zealand Government, The Treasury, 2011)
This paper examines the elasticity of tax revenue with respect to a marginal rate change, at both the individual and aggregate level. The roles of the elasticity of taxable income (the behavioural effect on taxable income of a tax rise) and the revenue elasticity (the structural effect on revenue of a change in taxable income) are highlighted. The revenue elasticity is the central concept in examining fiscal drag, but it has an additional role in the context of the revenue effects of tax changes when incomes respond to rate changes. Illustrations are provided using changes to the New Zealand income tax structure in the 2010 Budget. This reduced all marginal tax rates while leaving income thresholds unchanged.
Keywords: H24; H31; H26; 330; income tax revenue; elasticity of taxable income; revenue elasticity; Einkommensteuertarif; Steuereinnahmen; Elastizität; Steuerinzidenz; Anreiz; Neuseeland